2020
DOI: 10.1002/jcp.29706
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐derived extracellular vesicles suppress the fibroblast proliferation by downregulating FZD6 expression in fibroblasts via micrRNA‐29b‐3p in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF), a progressive and fatal lung disease, usually leads to an irreversible distortion of the pulmonary structure. The functional roles of bone marrow‐derived mesenchymal stem cells (BMSC)‐secreted extracellular vesicles (EVs) in fibroblasts have been implicated, yet their actions in the treatment of IPF are not fully understood. This study investigated the roles of BMSC‐derived EVs expressing miR‐29b‐3p in fibroblasts in IPF treatment. EVs derived from BMSCs were successfully i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…Additionally, bioinformatics analysis has revealed that eighty-four peptides varied significantly between MSC-EV treatment and fibroblast-derived EV treatment with myeloid/monocyte cells [106]. More recently, Wan et al have conducted research on MSC-EV effects on pulmonary fibroblasts, and have demonstrated that the EVs suppress fibroblast proliferation, migration, invasion, and differentiation in IPF, confirmed by Cell Counting Kit (CCK-8), Transwell assay, and gain-and loss-of-function assays through overexpressing miR-29-3p [107].…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Additionally, bioinformatics analysis has revealed that eighty-four peptides varied significantly between MSC-EV treatment and fibroblast-derived EV treatment with myeloid/monocyte cells [106]. More recently, Wan et al have conducted research on MSC-EV effects on pulmonary fibroblasts, and have demonstrated that the EVs suppress fibroblast proliferation, migration, invasion, and differentiation in IPF, confirmed by Cell Counting Kit (CCK-8), Transwell assay, and gain-and loss-of-function assays through overexpressing miR-29-3p [107].…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…The PV1 antibody was conjugated to an antifibrotic small molecule and showed increased localisation of the small molecule to the lung and kidneys. 108 Wan et al 112 investigated bone marrow stem cell (BMSC) derived EVs as a potential treatment for IPF. They found that BMSC EVs with over-expressed miR-29b-3p could inhibit fibroblast activity.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…They found that BMSC EVs with over-expressed miR-29b-3p could inhibit fibroblast activity. 112 Mansouri et al 113 demonstrated the ability of MSC-EVs to alter the phenotype of bone-marrow monocyte, aiming to elicit the same anti-inflammatory phenotype in lung monocytes as a treatment for IPF. Dinh et al 114 used treated murine models of IPF with lung spheroid cell (LSC)-derived exosomes.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Several animal studies show promising results in treating pulmonary fibrosis with MSC or derivates thereof such as exosomes and extracellular vesicles (EVs), alleviating fibroblast activation and ECM deposition along with anti-inflammatory outcomes ( Reddy et al, 2016 ; Mansouri et al, 2019 ; Gad et al, 2020 ; Wan et al, 2020 ). Pre-clinical studies on COPD demonstrate that MSCs reduce inflammation and improve histological lung structure ( Cruz and Rocco, 2020 ), which have been translated into several human clinical trials for treatment of COPD( Ribeiro-Paes et al, 2011 ; Weiss et al, 2013 ; Stolk et al, 2016 ; de Oliveira et al, 2017 ; Armitage et al, 2018 ).…”
Section: Msc Based Therapy In Ipf and Copdmentioning
confidence: 99%